Alelopathy of Cenchrus clandestinus on common bean (Phaseolus vulgaris L.) germination - Velasco-Villabona, Sugey; Quevedo-García, Enrique; Chaparro-García, Amanda Lucía (Agronomía Mesoamericana, 2024)
Introduction. Weeds are one of the main problems in agricultural productivity due to their interactions with crops, such as alelopatic effects on germination. Objective. To evaluate the allelopathy of kikuyo grass (Cenchrus clandestinus) on the germination of beans (Phaseolus vulgaris L.) variety ICA Cerinza. Materials and methods. The study was conducted at the Quality Control Laboratory of the Universidad de Pamplona, Central Campus, Pamplona, Norte de Santander, Colombia, from May to August 2022. To each experimental unit (Petri dishe) with 12 been seeds, 6 mL of kikuyo aqueous extract (leaf, stem, and root) at three concentrations (1, 2.5, and 5 %), plus a control (0 %), were added, totaling 12 treatments. From day 0 to 12, the number of germinated seeds (NGS) was recorded, and the germination rate index (GRI) and germination index (IG) were calculated. The biomolecular profile of the aqueous extract was determined using the Fourier-transform spectroscopy. A completely randomized experimental design with a factorial arrangement (3x4), with repeated measures in each experimental unit, was employed. The intersuject factors were the organ type and concentration, while the intrasubject factor was the evaluation time (12 days). Results. Significant differences (p<0.001) were observed for NSG among treatments due to the concentration of the aqueous extract, as well as for IG, while GRI depended on the organ (p<0.05) and concentration (p<0.001), both negatively affected as the concentration increased. The infrared spectrum of the extract determined the presence of polyphenols, nitriles, and siloxanes. Conclusión. C. clandestinus affected NGS, GRI, and GI of P. vulgaris, with an allelopathic effect of the leaf aqueous extract at higher concentrations. Polyphenols, nitriles, and siloxanes associated with allelopathic effects were identified in the aqueous extracts.